A short review on polyurethane-based nanocomposites for various applications - Marina, Mohamad; Jeefferie, Abd Razak; Noraiham, Mohamad; Sahrim, Haji Ahmad; Ramli, Junid; Puspitasari, Poppy (IOP Publishing Ltd, 2020)
In recent years, polyurethane (PU) has attracted researchers' attention due to their easily tailored properties to meet specific application requirements. PU and PU-based composites are being developed to be applied in various demanding fields such as aerospace, automotive, and electronics. This is because PU-based nanocomposites have numerous types of functional nanofiller integration. This has led to the advancement of polymer nanocomposite of PU with the inclusion of nanosised fillers for various specific purposes. In this short review article, the authors haves reviewed the fundamental or basic understanding of PU and several types of nanofillers used such as clay, carbon nanotubes, and graphene for PU-based nanocomposites development, as well as its potential applications.